2022
DOI: 10.1063/5.0074759
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-hemispherical pit array textured surface for increasing the efficiency of thin-film solar cells

Abstract: Enhancing light absorption is an important way for solar cells to increase the conversion efficiency. In this paper, we prepared a quasi-hemispherical pit array texture on the glass surface through the micro-fabrication process. Then, silicon thin-film (a-Si:H) solar cells were deposited on the other smooth surface. Pit array textured cells exhibit a higher short-circuit current density and power conversion efficiency than flat devices by ∼7% and 5%, respectively. The reflectance spectrum of textured solar cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, compared with traditional energy resources, solar energy experiences deficiencies such as high manufacturing cost and unideal transform efficiency, which seriously limit its wide application. To improve the conversion efficiency, researchers have developed light-trapping structures for various solar cells, such as nano/micro-pyramids [1][2][3][4], nanowires [5][6][7], nanocone [8][9][10][11][12], nanosphere [13][14][15][16], and porous silicon structures [17,18]. Light-trapping structures possess broadband optical absorption abilities, which can effectively lower the loss of light caused by reflection and raise the valid length of optical paths in the active layer of solar cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with traditional energy resources, solar energy experiences deficiencies such as high manufacturing cost and unideal transform efficiency, which seriously limit its wide application. To improve the conversion efficiency, researchers have developed light-trapping structures for various solar cells, such as nano/micro-pyramids [1][2][3][4], nanowires [5][6][7], nanocone [8][9][10][11][12], nanosphere [13][14][15][16], and porous silicon structures [17,18]. Light-trapping structures possess broadband optical absorption abilities, which can effectively lower the loss of light caused by reflection and raise the valid length of optical paths in the active layer of solar cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively recent reports found that optimal morphology is neither perfectly ordered nor totally random but a mixture of both categories [19,20]. Among the procedures to fabricate textures, one can mention: hot-embossing method [21], UV nanoimprint lithography [22], nanosphere lithography [23] and other microfabrication routes [24]. Few studies are focused on texturing of the classical glass cover by means of the aforementioned methods for better light management [24][25][26].…”
Section: Introductionmentioning
confidence: 99%